Pembinaan Financial Education Bagi Ibu Rumah Tangga - Hikmah Hikmah; Dian Efriyenti; Khadijah Khadijah (Jurnal Pengabdian Masyarakat (abdira), 2021)
Housewives have a very big role in determining the future, especially in the field of education. Therefore, there is a need for financial education for children and understanding of parents. Based on the observations of the servants before doing the service, housewives did not understand how to introduce financial education to children and families. This service will be carried out for 5 meetings with the material for each meeting will be different to solve existing problems. The methods given during this service are lectures, tutorials and exercises. The housewives of Bengkong Permai Housing after the service have knowledge and understanding related to financial education, this can be seen from the exercises carried out at the end of the meeting. It is hoped that the results of the activities carried out by housewives can be useful for families and introduce financial education to children and families in order to create good family financial health.